2014
DOI: 10.1371/journal.pone.0086610
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Diversities and Taxa Abundances in Soils along a Seven-Year Gradient of Potato Monoculture Using High Throughput Pyrosequencing Approach

Abstract: BackgroundPrevious studies have focused on linking soil community structure, diversity, or specific taxa to disturbances. Relatively little attention has been directed to crop monoculture soils, particularly potato monoculture. Information about microbial community changes over time between monoculture and non-monoculture treatments is lacking. Furthermore, few studies have examined microbial communities in potato monoculture soils using a high throughput pyrosequencing approach.Methodology/Principal FindingsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
60
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 53 publications
16
60
2
Order By: Relevance
“…The lower abundance of FOC in the pineapple treatment is in agreement with previous studies that have shown decreased FOC abundances linked to cultivar disease resistance (Hopkins and Elmstrom, 1984;Li et al, 2014;Liu et al, 2014). A higher abundance of Gymnopilus, belonging to Strophariaceae, was observed in the pineapple soils versus maize.…”
Section: Discussionsupporting
confidence: 91%
“…The lower abundance of FOC in the pineapple treatment is in agreement with previous studies that have shown decreased FOC abundances linked to cultivar disease resistance (Hopkins and Elmstrom, 1984;Li et al, 2014;Liu et al, 2014). A higher abundance of Gymnopilus, belonging to Strophariaceae, was observed in the pineapple soils versus maize.…”
Section: Discussionsupporting
confidence: 91%
“…The same results have been observed in different types of soil (BuĂŠe et al, 2009;Lauber et al, 2008). However, this study showed that Basidiomycota accounted for 17.96% of the microbial abundance in our samples, in contrast to only 0.6% in the soil samples investigated by Liu et al (2014). The difference may be attributed to the difference of soil type; moreover, the use of different amplified fragments and different sequence databases for the phylogenetic assignment may also affect the experimental results about the contribution of Basidiomycota.…”
Section: Discussionsupporting
confidence: 76%
“…There were some differences in our results and other reported results. For example, it was reported that soil fungal diversity increased during continuous cropping with peanut (Liu et al, 2014) and during long-term monoculture of vanilla, while no obvious distinctions were observed among the bacteria (Xiong et al, 2014). Therefore, the change of soil fungal diversity may be different between aquatic plant environment and terrestrial plant environment.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous monoculture of tomato is more common in protected cultivation than in non-protected cultivation [11]. However, the continuous cropping of a single species leads to several soil-related obstacles [12,13], manifesting as retarded plant growth, serious pest and disease damage, low crop productivity, and soil degradation [14,15]. Numerous studies have asserted that the mechanisms of these obstacles mainly include changes in soil physicochemical properties, destruction of the ecological environment, and plant autotoxicity [16,17].…”
Section: Introductionmentioning
confidence: 99%